Strategi Pembelajaran IPA Berbasis Konkret untuk Mengatasi Kesulitan Berpikir Abstrak pada Siswa SD dalam Memahami Konsep Ilmiah - Ika putra viratama; Andrea Gafiria Permata Putri; Miske Aprillia Herawati; Nur Ihwanul Karim; Diva Amilia Ramadhani (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study aims to quantitatively test the effectiveness of a concrete object-based science learning strategy in improving students' understanding of abstract concepts and addressing their learning difficulties in science at the elementary school level. By implementing a quasi-experimental design, this study compared a group of students who learned science through real media and concrete objects and through contextual, hands-on experiences with a control group. The hypothesis in this study states that students in the experimental group will show a significant increase in their science concept understanding test scores, measurable development of critical thinking skills, and a decrease in their detected learning difficulties, when compared with the control group. The tools employed in this research included a standardized test for understanding science concepts, a rubric designed to evaluate critical thinking abilities, and a Likert-scale survey to gauge students' opinions on how difficult they found the material. The quantitative data collected will be examined using an independent t-test to compare the average scores of different groups and a paired t-test to measure progress within the experimental group. Preliminary findings indicate that complex and abstract science materials are often the main cause of learning difficulties for elementary school students, which is in line with the limitations in abstract reasoning at that age, as stated in Piaget's theory of cognitive development. Therefore, this concrete method is expected to significantly increase student participation, help them absorb new information into their existing understanding, and in turn, improve their learning outcomes. The results of this study will provide concrete evidence of the positive effects of using concrete media and direct experiences in science learning at the elementary school level, as well as provide data-based suggestions for curriculum development and better teaching practices to address gaps in students' understanding of abstract concepts.